Avaliação do ruído e temperatura na aplicação de concreto betuminoso usinado quente: CBUQ - Garcia, Cristiane Santiago Crucillo (2014)
With this research we sought to assess the working conditions under which employees paving exclusively evaluating the enforcement team of asphalt concrete hot machined, are set forth with respect to noise and temperature. The noise measurements were performed using a decibel meter and measurements for verification of heat through the dry bulb thermometers, wet bulb and globe, to verify the environment that the worker is exposed. For the analysis of thermal overload , the index wet bulb globe thermometer ( WBGT ) was used because it takes into account all environmental and physiological factors homeotherm balance and is currently used by ACGIH ( American Conference of Governmental Industrial Hygienists ) , NIOSH (National Institute for Occupational Safety and Health ) and NR - 15 Ordinance n.3.214 Safety and Occupational Medicine. Series: Books of Law. Atlas .73rd .Edition, 2014. Given the measurements it was observed that both the measurement noise as temperature measurement, both gave results above allowed.